1992
DOI: 10.1172/jci115765
|View full text |Cite
|
Sign up to set email alerts
|

Platelet activating factor mediates interleukin-2-induced lung injury in the rat.

Abstract: Interleukin-2 was recently shown to cause acute lung injury characterized by microvascular permeability defect, interstitial edema, and leukosequestration. Similar responses can also be produced by platelet activating factor (PAF). Thus, the present study aimed to examine whether PAF plays a key role in the development of IL-2-induced lung injury in the anesthetized rat. Intravenous infusion (60 min) of recombinant human IL-2 at 10'-10' U/rat (a = 7-9) dose-dependently elevated lung water content (27±1%, P < 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 36 publications
(14 reference statements)
0
7
0
Order By: Relevance
“…Initial preclinical studies suggested that microvasculature damage, causing a generalized increase of vascular permeability to albumin, was the basic mechanism of rIL-2-induced NCPE [25]. Subsequent studies went into more detail and associated the systemic administration of rIL-2 with lesions of venous and capillary endothelia, alveolar basement membrane, and type I epithelial cells in animals, while leukocyte or platelet activation, generation of free radicals, and activation of the complement system have also been suggested to be involved in its pathogenesis [92][93][94][95][96][97]. Despite a widening evidence of the involvement of various cytokines released by activated lymphoid cells in the pathogenesis of rIL-2-induced NCPE, the exact mechanism of the damaging events that drive this clinical syndrome remain unclear [23,33].…”
Section: Pathophysiologymentioning
confidence: 99%
“…Initial preclinical studies suggested that microvasculature damage, causing a generalized increase of vascular permeability to albumin, was the basic mechanism of rIL-2-induced NCPE [25]. Subsequent studies went into more detail and associated the systemic administration of rIL-2 with lesions of venous and capillary endothelia, alveolar basement membrane, and type I epithelial cells in animals, while leukocyte or platelet activation, generation of free radicals, and activation of the complement system have also been suggested to be involved in its pathogenesis [92][93][94][95][96][97]. Despite a widening evidence of the involvement of various cytokines released by activated lymphoid cells in the pathogenesis of rIL-2-induced NCPE, the exact mechanism of the damaging events that drive this clinical syndrome remain unclear [23,33].…”
Section: Pathophysiologymentioning
confidence: 99%
“…Therapeutic use of the lymphocyte-derived cytokine interleukin-2 (IL-2) has been associated with the development of bronchovascular oedema (Ferro et al 1989). The mechanism(s) by which IL-2 mediates increased microvascular permeability are not clear, but may include both direct toxic effects on vascular endothelial cells (Downie et al 1992) and indirect effects via activation of other cells and/or release of secondary mediators including TxAz (Ferro et al 1989) and PAF (Rabinovici et al 1992).…”
Section: Interleukin-2mentioning
confidence: 99%
“…Rat has been extensively used to examine many physiological and pharmacological processes in which PAF was suspected to act as a mediator. PAF effects have been described in a variety of rat tissues such as leukocytes (Hwang et al, 1991), osteoclasts (Wood et al, 1991), lung (Rabinovici et al, 1992), digestive tract (Caplan et al, 1990;Filep et al, 1992), liver (Gandhi et al, 1992;Chao et al, 1992), kidney (Perico and Remuzzi, 1990;Handa et al, 1991), heart (Rayner et al, 1991 ;Massey et al, 1991), spleen (Pignol et al, 1990) and brain Arai and Lynch, 1992;Clark et al, 2992;Wieraszko et al, 1993). Rat platelets, however, were reported to be insensitive to PAF (Namm et al, 1982;Inarrea et al, 1984;Klee et al, 1991), contrasting highly with other species such as human or rabbit, where PAF induces prominent platelet aggregation, hence its name.…”
mentioning
confidence: 99%